Investigation of isomer ratios yields for 109Pd and 112In nucleus for e1-giant resonance range in (γ, n)-reactions - V. A. Zheltonozhsky; V. M. Mazur; Z. M. Bigan; D. M. Symochko (Ядерна фізика та енергетика)
Within 9 - 18 MeV energy range the dependence of isomer yield ratios and cross-sections on gamma-quanta energy in the 110Pd(γ, n)109m,gPd and 113In(γ, n)112m,gIn reactions have been studied. The experimental results are compared with those calculated within the framework of cascade-evaporation model.